Hydrogen‐Bonds‐Mediated Nanomedicine: Design, Synthesis, and Applications. Issue 18 (9th June 2022) - Chen, Senbin; Wu, Yanggui; Lortie, Frédéric; Bernard, Julien; Binder, Wolfgang H.; Zhu, Jintao
Abstract: Among the various challenges in medicine, diagnosis, complete cure, and healing of cancers remain difficult given the heterogeneity and complexity of such a disease. Differing from conventional platforms with often unsatisfactory theranostic capabilities, the contribution of supramolecular interactions, such as hydrogen‐bonds (H‐bonds), to cancer nanotheranostics opens new perspectives for the design of biomedical materials, exhibiting remarkable properties and easier processability. Thanks to their dynamic characteristics, a feature generally observed for noncovalent interactions, H‐bonding (macro)molecules can be used as supramolecular motifs for yielding drug‐ and diagnostic carriers that possess attractive features, arising from the combination of assembled nanoplatforms and the responsiveness of H‐bonds. Thus, H‐bonded nanomedicine provides a rich toolbox that is useful to fulfill biomedical needs with unique advantages in early‐stage diagnosis and therapy, demonstrating the promising potential in clinical translations and applications. Here the design and synthetic routes toward H‐bonded nanomedicines, focus on the growing understanding of the structure‐function relationship for efficient cancer treatment are summarized. A guidance for designing new H‐bonded intelligent theranostic agents is proposed, to inspire more successful explorations of cancer nanotheranostics and finally to promote potential clinical translations. Abstract : Hydrogen‐bonds (H‐bonds) bridge artificial and biological sciences, implementing dynamic properties into materials and (macro)molecules, which cannot be achieved via purely covalent bonds. In this review, the current state‐of‐the‐art for designing novel H‐bonded nanomedicines for precise diagnosis, and targeted therapeutic drugs delivery are highlighted.